2009
DOI: 10.1080/17450390903020430
|View full text |Cite
|
Sign up to set email alerts
|

Effect of zeolite A on rumen fermentation and phosphorus metabolism in dairy cows

Abstract: The aim of the present study was to determine the effect of zeolite A on several physiological parameters and on mineral metabolism in the rumino-intestinal-tract of cows. Eight double fistulated (rumen and proximal duodenum) cows were fed maize silage, grass silage and concentrate. Zeolite A was added to the ration over a period of three weeks at 0, 10 and 20 g/kg dry matter (DM). The daily feed amounts were adjusted to the current performance and varied between 3.9 and 15.5 kg/d. Rumen fluid, duodenal chyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
13
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
4
13
0
1
Order By: Relevance
“…This is confirmed by the results of previous studies in ruminants where no significant effect of clinoptilolite on blood serum P was recorded [5,20,23,24]. On the contrary, the supplementation of synthetic zeolite A seems to have a negative effect on phosphorus metabolism, which is reflected in the low-serum P concentration [9,[25][26][27].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is confirmed by the results of previous studies in ruminants where no significant effect of clinoptilolite on blood serum P was recorded [5,20,23,24]. On the contrary, the supplementation of synthetic zeolite A seems to have a negative effect on phosphorus metabolism, which is reflected in the low-serum P concentration [9,[25][26][27].…”
Section: Discussionsupporting
confidence: 93%
“…The exact mechanism by which clinoptilolite might affect the molar proportion of volatile fatty acids in rumen is currently unknown and needs further investigation. Similar alterations of the molar proportions of the volatile fatty acids have been recorded in previous experiments as well [9,17,18], but other researchers observed that clinoptilolite increased the proportion of propionate [15,16]. However, in the latter experiments clinoptilolite was added to high-concentrate diets and not at high-roughage diets as at the present study.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations